Nonlinear standing waves in miniature acoustic resonators - Luo, Cheng (2008)
This thesis presents a study on nonlinear resonance oscillations in shaped resonators. The main objective of the study is to investigate acoustic characteristics of nonlinear standing waves in small-size and miniature resonators.